"I Don't Have Time to Sit and Talk with Them": Hospitalists' Perspectives on Palliative Care Consultation for Patients with Dementia. Issue 10 (3rd August 2020) - Courtright, Katherine R.; Srinivasan, Trishya L.; Madden, Vanessa L.; Karlawish, Jason; Szymanski, Stephanie; Hill, Sarah H.; Halpern, Scott D.; Ersek, Mary
Abstract : BACKGROUND/OBJECTIVES: Specialty palliative care for hospitalized patients with dementia is widely recommended and may improve outcomes, yet rates of consultation remain low. We sought to describe hospitalists' decision‐making regarding palliative care consultation for patients with dementia. DESIGN: Descriptive qualitative study. SETTING: Seven hospitals within a national nonprofit health system. PARTICIPANTS: Hospitalist physicians. MEASUREMENTS: Individual semistructured interviews. We used thematic analysis to explore factors that influence hospitalists' decision to consult palliative care for patients with dementia. RESULTS: A total of 171 hospitalists were eligible to participate, and 28 (16%) were interviewed; 17 (61%) were male, 16 (57%) were white, and 18 (64%) were in practice less than 10 years. Overall, hospitalists' decisions to consult palliative care for patients with dementia were influenced by multiple factors across four themes: patient, family caregiver, hospitalist, and organization. Consultation was typically only considered for patients with advanced disease, particularly those receiving aggressive care or with family communication needs (navigating conflicts around goals of care and improving disease and prognostic understanding). Hospitalists' limited time and, for some, a lack of confidence in palliative care skills were strong drivers of consultation. Palliative care needs notwithstanding, most hospitalists would not request consultation if they perceived families would be resistant to it or had limited availability or involvement in caregiving. Additional barriers to referral at the organization level included a hospital culture that conflated palliative and end‐of‐life care and busy palliative care teams at some hospitals. CONCLUSION: Hospitalists described a complex consultation decision process for involving palliative care specialists in the care of patients with dementia. Systematic identification of hospitalized patients with dementia most likely to benefit from palliative care consultation and strategies to overcome modifiable family and organization barriers are needed. J Am Geriatr Soc 68:2365–2372, 2020.